Comparative impact of synthetic and natural animal-derived carotenoids on growth, feed utilization, and pigment enhancement in Amphiprion ocellaris - Dung Van Tran; Trang Le Thi Tran; Nam Xuan Doan; Thanh Trung Dang; Nhan Thai Hua; Hung Quoc Pham (Fisheries and Aquatic Sciences)
Coloration significantly influences the perceived value and consumer acceptance of ornamental fish within the aquarist community. Carotenoids, pigments essential for coloration, are primarily responsible for the vibrant hues observed in ornamental fish. This investigation assessed the effects of supplementing natural carotenoids (extracted from chicken eggs, shrimp shells, copepods, and golden apple snail eggs) versus synthetic astaxanthin (Carophyll Pink, 10%) on the growth, feed utilization, and color enhancement in juvenile clownfish (Amphiprion ocellaris). Juvenile specimens (3.14 ± 0.02 cm in total length and 0.54 ± 0.02 g in body weight) were subjected to five carotenoid-enriched diets, each supplemented with an identical dosage of 250 mg/kg of feed, in addition to a control group without supplementation. The fish were cultivated in glass tanks (60 liters per tank), each housing 15 individuals, with triplicate tanks per dietary treatment over a period of 75 days. Findings revealed that supplementation with both natural and synthetic carotenoids significantly improved growth and coloration over the control (p < 0.05). Notably, carotenoids derived from shrimp shells and copepods outperformed synthetic astaxanthin in enhancing growth and feed efficiency. Additionally, the skin redness intensity and the accumulated carotenoid concentration were highest in these two natural treatments, with no significant difference compared to the synthetic astaxanthin group (p > 0.05). This research highlights that supplementing with natural carotenoids from shrimp shells and copepods is a viable and effective method to augment growth and coloration in clownfish, suggesting a potential alternative to synthetic astaxanthin to elevate the quality and commercial value of farmed marine ornamental fish.